Crystallography and surface morphology evolution of thermally treated Cu thin films on SiO2/Si substrates - Hurtado Salinas, Daniel (2010)
In this work, we study the crystallization and surface morphology of Cu thin films (exposed to environment) growth on SiO2/Si subsstrates. The samples thermally treated using a tubular furnace bet ween temperature range 250-1000ºC during an elapsed time of 3 hours, after was cooling to a rate of 1.4ºC/min. The crystalization process was measured by X-ray difraction (XRD), meanwhile the surface morphology was observed with scanning electron microscopy (SEM). The results was analyzed and permit us to know the temperature dependecy of the dynamics of surface atoms on the Cu/SiO2 system, are the range between 400-500ºC. During the annealing an oxidation process on sample surfaces occur and the presence of Cu silicides are detected.